The Impact of Contract Farming on The Production Risk of Coffee Farming in Lampung - Basri, Moh. Hasan; Fariyanti, Anna; Suharno (Jurnal Manajemen dan Agribisnis, 2024)
Background: One of Indonesia’s largest producers of robusta coffee, Lampung Province still faces challenges and risks in coffee productivity. Coffee productivity in Lampung fluctuates and tends to decrease each year. Contract farming is one of the solutions to overcome these issues. Purpose: This research aims to analyze the impact of contract farming on production and production risk in robusta coffee farming in Lampung Province. Design/methodology/approach: The data used in this study is secondary data obtained from the Project Cooperation Agreement (PCA). This research uses a sample size of 99 contract farmers and 104 non-contract farmers. The research analysis method uses the OLS estimation approach to estimate the production function and MLE estimation for the production risk function. Findings/Result: The results showed that contract farming significantly and positively impacts coffee production outcomes. Conversely, contract farming has a significant and positive influence on production risk. Meanwhile, factors that reduce production risk include land area and labor. Contract farming increases production yields, but it also raises production risks. This insight is crucial for farmers considering contract farming, as it underscores the need for comprehensive risk management strategies and productivity enhancements. Conclusion: Contract farming in Lampung has successfully increased coffee production through input assistance and access to technology. However, it has also increased production risks due to the incomplete implementation of contracts by farmers. To mitigate these risks, attention must be given to factors such as land area and labor, which have been proven to reduce production risks. Originality/value (State of the art): Contract farming in Lampung has shown great potential in increasing coffee production. However, the incomplete implementation of contracts by farmers has increased production risks. This study emphasizes the importance of risk management in contract farming. To enhance effectiveness, full implementation of contract terms and better risk management are necessary. Keywords: coffee productivity, contract farming, Lampung Province, production risk, robusta coffee